A Personal Simple Blog System Based on Gradle and Springboot Implementation - Zhang, Pan (Journal of Theory and Practice of Engineering Science, 2024)
With the development of the Internet, the emergence of blogs gives more opportunities to express their views and information to others in life. In a blog, you can freely express your thoughts, emotions, and make friends with different people. The blog system quickly became a platform for individuals to express their opinions. This blog system is mainly implemented using Gradle and Springboot in Java, with the help of the thymeleaf template engine.